2021
DOI: 10.1371/journal.pone.0247078
|View full text |Cite
|
Sign up to set email alerts
|

Health, lifestyle and sociodemographic characteristics are associated with Brazilian dietary patterns: Brazilian National Health Survey

Abstract: This study aimed to identify Brazilian dietary patterns and their associations with health, lifestyle and sociodemographic characteristics. Data from the Brazilian National Health Survey conducted in 2013 were used. A questionnaire was applied containing 22 items related to dietary consumption. Dietary patterns were determined through factor analysis (FA). Poisson regression models, with robust variance, were used to identify associations between dietary patterns and independents variables. Statistical signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 73 publications
7
7
0
1
Order By: Relevance
“…The DP identified in the present study were consistent with other previously described DP in the region [ 31 , 32 , 33 , 34 ]. The Meat DP identified in our study consisted of foods that characterize Uruguayan eating habits such as red and barbecued meat, bread, and soft drinks.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The DP identified in the present study were consistent with other previously described DP in the region [ 31 , 32 , 33 , 34 ]. The Meat DP identified in our study consisted of foods that characterize Uruguayan eating habits such as red and barbecued meat, bread, and soft drinks.…”
Section: Discussionsupporting
confidence: 93%
“…A previous report suggested that the modest protective effect of healthier DPs is often related to complementary health behaviors [ 11 ]. In our study, adherence to the Prudent DP was more common among participants with higher education (particularly in the older ones), similar to a previous study [ 34 ], which could reflect that they are able to better understand the importance of healthy eating. The Cereal and Mate DP identified in this study emerged with the mate infusion beverage as an important component.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Suboptimal dietary intake of antioxidant vitamins, particularly vitamins A, C, and E, and carotenoids, and other antioxidants such as selenium, zinc and flavonoids, may adversely affect the modulation of oxidative lung stimuli. 86 , 88 In contrast, higher intakes may have beneficial effects on the modulation of oxidative lung stimuli, thus decreasing airway hyperactivity, wheezing symptoms, and asthma. 89 For example, low serum zinc levels were associated with a doubling of wheeze prevalence.…”
Section: Lifestyle and Behaviourmentioning
confidence: 99%